Pengaruh Persepsi Harga, Lokasi dan Variasi Produk Terhadap Keputusan Pembelian: Studi Kasus Pada PD. Gudmal Toko Bahan Sandal Kota Tasikmalaya - Asep Nizar Assaukani; Depy Muhamad Pauzy; Suci Putri Lestari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The purpose of this study was to determine the effect of price perceptions, locations and product variety on purchasing decisions at PD Gudmal Sandal Material Store. The research used is quantitative research with a survey method to 88 respondents of PD Gudmal Sandal Material Store who live in Tasikmalaya city. The types of data used are primary data and secondary data. The data analysis technique uses multiple linear regression analysis.The results of this test prove that simultaneously perceptions of price, locations and product variety have a significant influence. And partially, price perception has a significant effect on purchasing decisions, location has a significant effect on purchasing decisions, and product variety has a significant effect on purchasing decisions at PD Gudmal Sandal Material Store.